2015
DOI: 10.1021/acs.langmuir.5b00043
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Monodisperse Hierarchical Lipid Particles Utilizing Microfluidic Droplets in a Nonequilibrium State

Abstract: A new microfluidic process was used to generate unique micrometer-sized hierarchical lipid particles having spherical lipid-core and multilamellar-shell structures. The process includes three steps: (1) formation of monodisperse droplets in a nonequilibrium state at a microchannel confluence, using a phospholipid-containing water-soluble organic solvent as the dispersed phase and water as the continuous phase; (2) dissolution of the organic solvent of the droplet into the continuous phase and concentration of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…For example, it was shown that using a better water-miscible compound like ethyl acetate (solubility: 64–80 gl −1 (ref. 37 )) produces multilamellar thick-shelled lipid particles 38 . This result is similar to the one we obtained using 2-butanol as the LO phase (solubility: 181 gl −1 (ref.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it was shown that using a better water-miscible compound like ethyl acetate (solubility: 64–80 gl −1 (ref. 37 )) produces multilamellar thick-shelled lipid particles 38 . This result is similar to the one we obtained using 2-butanol as the LO phase (solubility: 181 gl −1 (ref.…”
Section: Discussionmentioning
confidence: 99%
“…The principle of LNP production by microfluidic platforms is similar to some of the conventional methods such as hydration and organic solvent injection. Utilization of fluid dynamics mixing, the interface of the microfluidic devices, and the shape of the microfluidic channels effectively assisted the production of the LNPs with desirable properties. ,, Kitazoe et al designed a microfluidic device with one inlet and 13 outlets to produce LNPs encapsulating pDNA. In this study, lipid films blended with cationic polymer (Polylysine) were coated on the inner surface of the glass channels before injecting pDNA to hydrate the lipid film.…”
Section: Applications Of Microfluidic Techniques In Drug Deliverymentioning
confidence: 99%
“…A similar technique to produce small alginate particles was also reported by Pittermannova et al (2016), wherein 1-undecanol with a surfactant was used as the continuous phase. The usage of this non-equilibrium droplet system has been applied to the production of other types of microparticles, including polymeric (Ono et al, 2014), lipid (Mizuno et al, 2015), protein Yajima et al, 2017), and carbon nanotube particles (Tomii et al, 2017), demonstrating its versatility and usefulness.…”
Section: Particle Production Using Miscible Water-oil Two Phase Owsmentioning
confidence: 99%